Highly efficient removal of phosphate from aqueous media by pomegranate peel co-doping with ferric chloride and lanthanum hydroxide nanoparticles. (10th April 2021) - Akram, Muhammad; Xu, Xing; Gao, Baoyu; Wang, Shue; Khan, Rizwan; Yue, Qinyan; Duan, Pijun; Dan, Hongbing; Pan, Jingwen
Abstract: The low phosphate content in the surface water is considered a pollutant that promotes algae reproduction and leads to eutrophication. Bimetallic Fe/La nanoparticles doped on pomegranate fiber (Fe/La Peel) were fabricated by solvothermal synthesis method and applied as biosorbent for phosphate removal in this study. Fe–La/Peel had an irregular and rough surface with a specific surface area of 93.18 m 2 /g and its surface was uniformly covered with Fe and La, providing potential adsorption sites for phosphate uptake. At the pH 2.91, the highest capacity of Fe/Peel, La/Peel and Fe–La/Peel were 13.91 mg/g, 38.86 mg/g and 44.5 mg/g, respectively. Batch adsorption experiments indicated that Fe–La/Peel biosorbent had excellent adsorption ability. In batch adsorption experiment, highest adsorption capacities of Fe–La/Peel fitted by Langmuir and Sips isotherms were 75.09 mg/g and 78.99 mg/g at 323 K, respectively. The total lowest metal leaching of Fe/La Peel was found 0.054 μg/mL under alkali condition, and the highest metal leaching was determined 8.13 μg/mL under acidic condition. The adsorption performance of Fe/La Peel was better than those La/Peel and Fe/Peel at the same pH levels. Phosphate capture by Fe–La/Peel bio-nanocomposite was a homogeneous adsorption process and increased capacity with the rising temperature. At neutral pH, phosphate uptake by Fe–La/Peel could maintain high efficiency and metal leaching was almost negligible. The preferential phosphate adsorption by Fe–La/Peel can also be achieved in the same magnitudes of coexisting anions (Cl −, NO3 −, HCO3 − ). And the adsorption capacity was reduced to less than 20% in the presence of electrolytes. These results showed that Fe–La/Peel has the potential to be used for environmental remediation to remove phosphate from the wastewater. Graphical abstract: Image 1 Highlights: A novel biosorbent containing bimetallic hydroxide nanocomposite was prepared. The preferential phosphate adsorption can be achieved in the presence of coexisting anions. The rest of the electrolytes were reduced to less than 20% adsorption capacity. At neutral pH, phosphate could be effective remove by Fe–La/Peel with less metal leaching.